SIKAP TERHADAP PERILAKU SEKSUAL PRANIKAH DITINJAU DARI RELIGIUSITAS DAN KONFORMITAS PADA REMAJA - Ulum, Bahrul; Hadiwirawan, Olivia (Noetic Psychology, 2015)
Abstract. Attitudes toward premarital sexual behavior is the tendency of perception and reaction to the feeling that support an action that is based on the inner urge to achieve sexual satisfaction in unmarried, illegal, circumstances. Premarital sexual behavior can be controlled by the presence of social control and religious behavior. In addition, conformity is another factor. This study aimed to review the role of religious behavior and conformity to predict adolescencesâ attitudes toward premarital sexual behavior in Jakarta by using a quantitative approach. The samples in this study were teenagers in South Jakarta, with cluster random sampling as a technique. For measurement this study used the scale of attitudes toward premarital sexual behavior, religiosity scale, and the scale of conformity. The results showed that religiosity and conformity can predict attitudes toward premarital sexual behavior (R = 0.534) with the value (F= 36.293) and significance (p = â¤ .01). Contributions made by religiosity and conformity in predicting attitudes toward premarital sexual behavior amounted to 27.7%, while 72.3% attitudes toward premarital sexual behavior predicted by other variables outside of this research.Keywords: attitudes toward premarital, adolescents, conformity, religiosity, unmarried sexual behavior Â